G etting to Implementation for HIV Pre-Exposure Prophylaxis (GTI-PrEP): A data-driven approach to PrEP prescribing - Shari S. Rogal; Brittney Neely; Monica Merante; Karen Slazinski; Lorenzo McFarland; Christina Brodkorb; Jada Cooper; Carolyn Lamorte; Sandra Gibson; Emily Comstock; Jamie Morano; Marissa Maier; et al. (Implementation Science Communications)
Abstract Background Pre-Exposure Prophylaxis (PrEP) dramatically reduces the likelihood of acquiring human immunodeficiency virus (HIV), yet it remains under-prescribed, particularly for people in communities with high HIV incidence. While implementation science and health services researchers aim to address disparities in care, few interventions have proven effective in doing so. We aimed to identify implementation strategies associated with higher PrEP prescribing rates and pilot test a tailored intervention as a proof-of-concept in a single Veterans Health Administration (VA) facility. Methods VA clinicians were surveyed using an instrument derived from the Evidence-based Recommendations for Implementing Change taxonomy to assess the use of various strategies for PrEP in fiscal years 2019–2021. Correlational analyses identified the strategies associated with the frequency of PrEP prescribing and semi-structured interviews with personnel from 11 VA medical facilities with high PrEP prescribing refined and manualized these strategies into the Getting to Implementation (GTI)-PrEP playbook. The playbook was subsequently pilot tested in a VA facility with high new HIV diagnosis rates and low PrEP prescribing rates. Results The clinician survey collected 157 responses from 95 unique VA facilities on implementation strategy use. Analysis identified eight strategies significantly associated with PrEP prescribing, including: networking, clinician education, clinical support tools, dashboard utilization, telehealth, pharmacist involvement, direct patient engagement, and enhanced sexual health history taking. In the pilot study, the site completed the GTI-PrEP Playbook with high fidelity and newly implemented seven of the eight strategies, achieving a 363% increase in PrEP prescribing rates among Black Veterans over the one-year period. Conclusions This multi-year national evaluation identified a core subset of effective implementation strategies for increasing PrEP prescribing. The process of empirically specifying these strategies and pilot testing them through the GTI-PrEP playbook demonstrates a promising, data-driven approach to improve PrEP prescribing rates and reduce racial disparities in HIV prevention.